Medical imaging : artificial intelligence, image recognition, and machine learning techniques - Santosh, K. C.; Antani, Sameer; Guru, DS; Dey, Nilanjan (Boca Raton: CRC Press, 2019)
The book discusses varied topics pertaining to advanced or up-to-date techniques in medical imaging using artificial intelligence (AI), image recognition (IR) and machine learning (ML) algorithms/techniques. Further, coverage includes analysis of chest radiographs (chest x-rays) via stacked generalization models, TB type detection using slice separation approach, brain tumor image segmentation via deep learning, mammogram mass separation, epileptic seizures, breast ultrasound images, knee joint x-ray images, bone fracture detection and labeling, and diabetic retinopathy. It also reviews 3D imaging in biomedical applications and pathological medical imaging.
Preface -- Editors -- 1. A novel stacked model ensemble for improved Tuberculosis (TB) detection in chest radiographs -- 2. The Role of Artificial Intelligence (AI) in Medical Imaging: General Radiologic and Urologic Applications -- 3. Early Detection of Epileptic Seizures based on scalp EEG signals -- 4. Fractal analysis in histology classification of non-small cell lung cancer -- 5. Multi feature-based classification of osteoarthritis in knee joint x ray images -- 6. Detection and classification of non-proliferative Diabetic Retinopathy Lesions -- 7. Segmentation and analysis of CT images for bone fracture detection and labelling -- 8. 3D imaging in biomedical applications: a systematic review -- 9. Evolution of Digital sliding of pathology in medical imaging -- 10. Pathological medical image segmentation: a quick review based on parametric techniques
Includes bibliographical references and index.
Keywords: Medical Imaging -- Artificial Intelligence; Image Recognition; Diagnostic Imaging